1997
DOI: 10.1523/jneurosci.17-20-08024.1997
|View full text |Cite
|
Sign up to set email alerts
|

Regulators of G-Protein Signaling (RGS) Proteins: Region-Specific Expression of Nine Subtypes in Rat Brain

Abstract: The recently discovered regulators of G-protein signaling (RGS) proteins potently modulate the functioning of heterotrimeric G-proteins by stimulating the GTPase activity of G-protein ␣ subunits. The mRNAs for numerous subtypes of putative RGS proteins have been identified in mammalian tissues, but little is known about their expression in brain. We performed a systematic survey of the localization of mRNAs encoding nine of these RGSs, RGS3-RGS11, in brain by in situ hybridization. Striking region-specific pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
408
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(441 citation statements)
references
References 33 publications
27
408
6
Order By: Relevance
“…These observations are similar to findings for mouse RGS5 (Chen et al 1997). Recently, the localization of nine rat RGSs, including RGS5, was investigated systematically in rat brain, using an in-situ hybridization technique; the RGS5 mRNA was expressed at lower density in rat brain than in the other tissues examined (Gold et al 1997).…”
Section: Resultssupporting
confidence: 80%
“…These observations are similar to findings for mouse RGS5 (Chen et al 1997). Recently, the localization of nine rat RGSs, including RGS5, was investigated systematically in rat brain, using an in-situ hybridization technique; the RGS5 mRNA was expressed at lower density in rat brain than in the other tissues examined (Gold et al 1997).…”
Section: Resultssupporting
confidence: 80%
“…Labeling densities for each region studied were taken from each brain section per animal (both hemispheres). Polynomial calibration curves were fitted to relative optical density values measured from known 14 C-labeled radioactive step standards (Amersham) that were coexposed to the film along with the brain tissue sections (Gold et al, 1997). For the Bcl-xl and Bax film autoradiograms, analysis was done on films exposed to the slides for 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…The partial cDNAs used as templates for riboprobe generation were generated by RT-PCR amplification using rat spleen and thymus cDNA as templates and Bcl-2-, Bclxl-, and Bax-specific primers with a T7 promoter sequence appended to the corresponding -3 0 primer as previously described (Gold et al, 1997). The cDNAs were confirmed by sequencing (Keck Facility, Yale University, CT).…”
Section: Riboprobesmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to that observed for other Gb1-4 subunits, the expression of Gb5 proteins is restricted to the brain (Watson et al, 1994;Fmost are found in the plasma membrane of neural cells (Watson et al, 1996;Betty et al, 1998). The mammalian R7 proteins are also found in the CNS (Gold et al, 1997;Snow et al, 1998; Thomas et al, 1998), where they are mostly associated with cell membranes (Rose et al, 2000;. In nervous tissues, the R7 proteins and Gb5 proteins are always found as dimers, indicating that this association is required for their GAP function on the corresponding Ga-GTP subunits (Snow et al, 1998;.…”
Section: Introductionmentioning
confidence: 94%